2021
DOI: 10.3390/ijms221910251
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mitophagy in Neurons and Glial Cells during Aging and Age-Related Disorders

Abstract: Aging is associated with a decline in cognitive function, which can partly be explained by the accumulation of damage to the brain cells over time. Neurons and glia undergo morphological and ultrastructure changes during aging. Over the past several years, it has become evident that at the cellular level, various hallmarks of an aging brain are closely related to mitophagy. The importance of mitochondria quality and quantity control through mitophagy is highlighted by the contribution that defects in mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 116 publications
0
11
0
1
Order By: Relevance
“…Diverse mitophagy-dependent signaling pathways have been established, many of which are conserved from Caenorhabditis elegans to humans (Egan et al, 2011 ; Fivenson et al, 2017 ; Kerr et al, 2017 ; Gustafsson and Dorn, 2019 ; Cai and Jeong, 2020 ; Wang et al, 2021b ). Mitophagy, a stress-response mechanism to suppress mitochondrion-dependent apoptosis for neuronal protection (Pan et al, 2021 ), is fairly fundamental for mitochondrial quality control, function recovery, and self-renewal, whose deficiency is revealed in AD iPSC-derived neurons, as well as hippocampal samples from the AD model mice and patients with AD, thus receiving growing attention as a promising mechanism for AD-targeted therapy of late years (Fang et al, 2014 , 2019 ; Xu et al, 2017 ; Tran and Reddy, 2020 ; Sukhorukov et al, 2021 ; Wang et al, 2021b ). Specifically, accumulating evidence implies that mitophagy deficit fails to maintain mitochondrial clearance (Kerr et al, 2017 ), axonal transport (Ashrafi and Schwarz, 2015 ), and synapse biosynthesis (Pan et al, 2021 ), which exacerbates neuroinflammation, Aβ and p-Tau deposition, and energy dysfunction, thereby promoting AD pathology and memory loss (Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse mitophagy-dependent signaling pathways have been established, many of which are conserved from Caenorhabditis elegans to humans (Egan et al, 2011 ; Fivenson et al, 2017 ; Kerr et al, 2017 ; Gustafsson and Dorn, 2019 ; Cai and Jeong, 2020 ; Wang et al, 2021b ). Mitophagy, a stress-response mechanism to suppress mitochondrion-dependent apoptosis for neuronal protection (Pan et al, 2021 ), is fairly fundamental for mitochondrial quality control, function recovery, and self-renewal, whose deficiency is revealed in AD iPSC-derived neurons, as well as hippocampal samples from the AD model mice and patients with AD, thus receiving growing attention as a promising mechanism for AD-targeted therapy of late years (Fang et al, 2014 , 2019 ; Xu et al, 2017 ; Tran and Reddy, 2020 ; Sukhorukov et al, 2021 ; Wang et al, 2021b ). Specifically, accumulating evidence implies that mitophagy deficit fails to maintain mitochondrial clearance (Kerr et al, 2017 ), axonal transport (Ashrafi and Schwarz, 2015 ), and synapse biosynthesis (Pan et al, 2021 ), which exacerbates neuroinflammation, Aβ and p-Tau deposition, and energy dysfunction, thereby promoting AD pathology and memory loss (Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction causes deficient energy production, oxidative stress and impaired cell signaling, all of which are associated with the pathogenesis of cognitive dysfunction. Clearance of dysfunctional mitochondria is important for maintaining normal neuronal function [ 114 , 115 ]. Following mitochondrial damage, autophagy is induced in three ways: ubiquitin-mediated mitochondrial phagocytosis, including PTEN-induced putative kinase 1 (PINK1)–Parkin (an E3 ubiquitin ligase)-dependent phagocytosis [ 116 ]; OMM receptor-mediated mitochondrial phagocytosis [ 117 ]; and lipid-mediated mitochondrial phagocytosis [ 118 ].…”
Section: Exercise Improves Mitochondrial Healthmentioning
confidence: 99%
“…Previous studies have revealed that Aβ can induce mitochondrial dysfunction [ 9 ]. Damaged and dysfunctional mitochondria are extensively removed by mitophagy, which is a central mechanism for the maintenance of organelle homeostasis in neural cells [ 10 ]. Since neurons rely on oxidative phosphorylation as the main energy source, mitochondrial function is of utmost importance in studies relating to NDs.…”
Section: Redox Homeostasis In Mitochondria and Production Of Rosmentioning
confidence: 99%